KEANEKARAGAMAN TUMBUHAN MANGROVE CAGAR ALAM PULAU SEMPU, JAWA TIMUR - Suhardjono Suhardjono (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
Thirty species which belong 18 families and 24 genera were recorded in mangrove areas of Ra’as, Air Tawar and Teluk Semut (Sempu Island, East Java). Twelve which included in IUCN List. The richest species diversity found in Ra’as (23 species) followed by Teluk Semut (17 species) and Fresh water (16 species). The dominant species of those areas were Ceriops tagal, Rhizophora apiculata, R. mucronata, Aegiceras corniculatum, Xylocarpus granatum and Excoecaria agallocha.